Telegram from William Randolph Hearst to Julia Morgan, February 1, 1921 - William Randolph Hearst::::::author::: (1921)
William Randolph Hearst asks Julia Morgan to change the color scheme for Mrs. Hearst's bedroom in House A, and to change the plan for the road up to the houses